2015
DOI: 10.1093/occmed/kqv119
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: factors contributing to burnout in dentistry

Abstract: This review identified several significant factors contributing to burnout in dentists and dental students. Further longitudinal and prospective studies are required to assess causation. Burnout should be considered a multifactorial phenomenon that can develop early in a dental career. Screening programmes and coping strategies might help to identify and prevent it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
98
3
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(125 citation statements)
references
References 28 publications
17
98
3
7
Order By: Relevance
“…Quality of education in Iraq is declining now due to poor preparation and weak training of teachers, lack of minimum standards of teaching materials, and (25), these factors together with that studied in this study could be the reasons for such high prevalence rate of burnout among primary school teachers in Basrah. We found that younger teachers and those with fewer years of service showed a significantly higher rate of burnout than their older and more experienced counterparts; this has also been reported in other studies (26)(27)(28). Younger teachers may be more idealistic and may feel inadequate and undervalued if they fail to reach their students (29,30).…”
Section: Discussionsupporting
confidence: 86%
“…Quality of education in Iraq is declining now due to poor preparation and weak training of teachers, lack of minimum standards of teaching materials, and (25), these factors together with that studied in this study could be the reasons for such high prevalence rate of burnout among primary school teachers in Basrah. We found that younger teachers and those with fewer years of service showed a significantly higher rate of burnout than their older and more experienced counterparts; this has also been reported in other studies (26)(27)(28). Younger teachers may be more idealistic and may feel inadequate and undervalued if they fail to reach their students (29,30).…”
Section: Discussionsupporting
confidence: 86%
“…23 Son zamanlarda yapılan çalışmalarda, diş hekimlerinde ve diş hekimliği öğrencilerinde anksiyetinin, depresyonun, kontrolsüz alkol alımı gibi kötü alışkanlıkların oldukça yüksek düzeyde olduğu saptanmıştır. 24,25 Huri ve ark.nın diş hekimleri üzerinde yürüttüğü bir çalışmada, ortalama BDI 13,32±8,51 olarak saptanmış ve bu değerin kadın hekimlerde anlamlı dü-zeyde yüksek olduğu bulunmuştur. 26 Bu çalışmaya katılan öğrencilerin ortalama BDI skoru 19,03±13,66 olarak saptanmış olup; kızlarda 18,38±12,98, erkeklerde ise 19,58±14,23'tür.…”
Section: Discussionunclassified
“…Despite that, dentists all over the world are subject to variety of occupational factors that affect their psychological and physical wellbeing. According to researchers all over the world, even young dentists face various psychological disorders such as burnout, stress, suicide and drug or alcohol addiction [1][2][3][4][5][6]. Majority of dentists (70-90%) suffer from various physical occupational disordersneck, shoulders, lower back and wrist pain is the most common [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Majority of dentists (70-90%) suffer from various physical occupational disordersneck, shoulders, lower back and wrist pain is the most common [7][8][9][10][11][12]. Lithuanian dentists face the same problemmany of them complain with back pain (91.0%), headache (88.7%), hand problems (83.1%) and chest pain (53.8%), 3 Vilnius University, Faculty of Medicine, Lithuania feel tired (82.6%) and tense (80.5%), suffer from anxiety (78.8%) or nervousness (89.2%), problems at work cause insomnia (74%) and awakening at night (78.8%); some dentists suffer from these symptoms constantly [13,14]. High volume workload is important stress trigger in clinical dentistry: 94.2% of Lithuania dentists claim experiencing negative health-related effects of long working hours and 41.7% of respondents experience these symptoms often or always [13].…”
Section: Introductionmentioning
confidence: 99%